Venom-derived peptide Mastoparan-1 eradicates planktonic and biofilm-embedded methicillin-resistant Staphylococcus aureus isolates. (June 2018) - Memariani, Hamed; Memariani, Mojtaba; Pourmand, Mohammad Reza
Abstract: During the past decade, cationic antimicrobial peptides (CAPs) have gained particular interest among researchers, since they often display broad-spectrum antimicrobial activity and low possibility of resistance emergence. This study aimed to investigate in vitro effectiveness of Mastoparan-1 (MP-1), a tetradecapeptide CAP from hornet venom, against methicillin-resistant Staphylococcus aureus (MRSA) isolates. MP-1 had a high propensity to form alpha-helix based on structural predictions. MP-1 was found to possess strong antimicrobial activities and weak cytotoxic effects. Multiple treatments of MRSA with MP-1 at sub-lethal dose did not induce resistance. At 4 × minimum bactericidal concentration (MBC), MP-1 eradicated bacteria within 60 min, whereas vancomycin was unable to eradicate MRSA even after 480 min of exposure, highlighting rapid bactericidal kinetics of MP-1. Treatment of bacteria with 2 × MBC of MP-1 caused a time-dependent increase in orange/red fluorescence intensity. Compared with vancomycin, MP-1 significantly reduced biofilm formation and diminished both biofilm biomass and viability of biofilm-embedded bacteria in a concentration-dependent manner. Taken together, the current data reveal not only that MP-1 is a potent bactericidal and antibiofilm agent, but also that it is less likely to invoke antimicrobial resistance, reinforcing further studies concerning the therapeutic applications of MP-1. Graphical abstract: Highlights: MP-1 exhibited strong antimicrobial activities against methicillin-resistant Staphylococcus aureus (MRSA) isolates. Multiple treatments of MRSA with MP-1 at sub-lethal dose (1/2 × MIC) did not induce resistance. Time-kill assay and fluorescence microscopy suggest that MP-1 can kill bacteria by membrane disruption. MP-1 reduced biofilm formation and diminished both biofilm biomass and viability of biofilm-embedded bacteria.